Potential uses of waste sludge in construction industry: A review - Johnson, O.A. (Maxwell Science Publications, 2014)
Waste generation and management is becoming a global challenge resulting into increased environmental concern. Waste management and recycle into a sustainable construction materials as proved to be an alternative for waste disposal helping out in the area of environmental pollution and economic. In recent years various type of waste has been used/reused in the development of sustainable construction materials. This study reviews various attempts that have been made to use sludge from different plants in construction industry. The mechanical and physical properties of the products, the environmental effect of the products and possible recommendations for future research was presented in the review. Â© Maxwell Scientific Organization, 2014.